Symmetrically Erupted Upper Fourth Molars and an Impacted Fifth Molar: A Case Report - Jian Shi; Ye Bi; Zhi Wu (Case Reports in Dentistry)
Conclusion: This report documents a rare case of symmetrically erupted fourth molars with an associated impacted fifth molar in the maxilla. The treatment strategy and surgical approach should be tailored to the patient’s symptoms and willingness to undergo the recommended procedures.